Analysis of Qicblat Direction at Jami Al Iman Mosque Sunan Geseng Loano Purworejo - Muhajir Muhajir; Imam Yahya; Frangky Suleman (Jurnal Ilmiah Al-Syir'ah, 2022)
This research is motivated by the questions from the community around the mosque about the Qibla direction's accuracy and the early history of purchasing the Qibla direction. This study examines the historical and astronomical aspects so that the community can accept the calculation of the Qibla direction. Does this research focus on how before shopping towards the Qibla of the Jami' Al-Iman Sunan Geseng Loano Mosque? How accurate? This empirical research uses historical and astronomical or astronomical approaches. The research subjects were mosque takmir and community leaders in Loano Purworejo. Data were collected through observation, interviews, and documentation and analyzed through astronomy and normative. The results of this study indicate that the Jami' Al-Iman Sunan Geseng Loano Mosque was founded by Sunan Geseng in 1443 AD, using the supernatural through the media of the priest's hole to determine the Qibla direction.